Thermal comfort and drag of a streamlined cycling helmet as a function of ventilation hole placement - Underwood, L.; Vircondelet, C.; Jermy, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
The ideal cycling helmet allows rapid heat loss from the head with minimum aerodynamic drag. The position and size of ventilation holes affect both heat loss and drag. An aero helmet with reconfigurable ventilation holes was mounted on a heated mannequin head in a wind tunnel at 16.7 m/s (60 km/h). Temperatures on the surface of the head, and the drag area (CdA), were measured for a number of different ventilation hole configurations. Surface temperature was lower immediately underneath the open ventilation holes, whatever configuration of open holes was tested. The average surface temperature was taken as a proxy for thermal comfort. Surprisingly, there was very little difference in average surface temperature with all holes open compared to no holes open, though the latter has lower drag. The lowest average surface temperatures were obtained when either the rearmost holes only were open or when only holes at the top of the helmet, halfway between the front and rear of the helmet, were open (referred to as `middle holes open`). Besides being effective in dissipating heat, these middle holes open configuration produced lower drag than the rear holes open configuration. However, we note from a previous study with this helmet that drag is more strongly affected by neck angle and how the helmet is fitted, than by the ventilation holes.